Peningkatan Literasi Digital melalui Pelatihan Komputer untuk Pengembangan UMKM di Desa Era 5.0 - Kusmanto; Febriani, Budi; Bobbi Kurniawan Nasution, Muhammad; Suryadi, Sudi (HIMPUNAN DOSEN GEMILANG INDONESIA, 2024)
Enhancing digital literacy is a crucial step in empowering MSMEs (Micro, Small, and Medium Enterprises) in rural areas to face challenges and seize opportunities in the 5.0 era. Digital literacy equips business actors with the ability to effectively utilize technology, such as conducting online marketing, managing digitally-based businesses, and accessing relevant information for business development. Through computer training, MSME actors can improve their skills in operating technological devices and optimizing the use of digital platforms. This training also supports MSMEs in adapting to technological changes, expanding market access, and increasing competitiveness. Thus, computer training for digital literacy serves as a strategic initiative to drive the development of rural MSMEs, ultimately contributing to local economic growth and strengthening the digital ecosystem in Indonesia..